2015
DOI: 10.1371/journal.pone.0126047
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Green Polyethylene by Pleurotus ostreatus

Abstract: We studied the biodegradation of green polyethylene (GP) by Pleurotus ostreatus. The GP was developed from renewable raw materials to help to reduce the emissions of greenhouse gases. However, little information regarding the biodegradation of GP discarded in the environment is available. P. ostreatus is a lignocellulolytic fungus that has been used in bioremediation processes for agroindustrial residues, pollutants, and recalcitrant compounds. Recently, we showed the potential of this fungus to degrade oxo-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 30 publications
(47 reference statements)
1
14
0
1
Order By: Relevance
“…However, after 4 months of exposure to sunlight we did not observe any fragmentation of the plastic bags, only the appearance of small cracks and the bleaching of the film were observed (Figure 2). Da Luz et al [14,15] also showed changes in mechanical properties of oxo-biodegradable and green polyethylene after 120 days of exposure to sunlight. According to them, this time of exposure is insufficient for other physical or chemical changes, concluding that the mechanical properties alterations, such as the reduction of breaking energy and elasticity facilitated the fungal colonization of plastic waste.…”
Section: Steps and Technics Used For Monitoring The Abiotic And Biotimentioning
confidence: 97%
See 4 more Smart Citations
“…However, after 4 months of exposure to sunlight we did not observe any fragmentation of the plastic bags, only the appearance of small cracks and the bleaching of the film were observed (Figure 2). Da Luz et al [14,15] also showed changes in mechanical properties of oxo-biodegradable and green polyethylene after 120 days of exposure to sunlight. According to them, this time of exposure is insufficient for other physical or chemical changes, concluding that the mechanical properties alterations, such as the reduction of breaking energy and elasticity facilitated the fungal colonization of plastic waste.…”
Section: Steps and Technics Used For Monitoring The Abiotic And Biotimentioning
confidence: 97%
“…In this micrograph, the red arrows show hyphae in plastic waste after 60 days of exposure to sunlight and 30 days of incubation. Da Luz et al [13][14][15] showed the formation of mycelium on the surface of d2w plastic and green polyethylene with different time of exposure to sunlight and of fungal incubation. They also reported the morphological characteristics of the mycelia of P. ostreatus PLO6.…”
Section: Steps and Technics Used For Monitoring The Abiotic And Biotimentioning
confidence: 99%
See 3 more Smart Citations